Active Ageing and Physical Activity : Guidelines, Functional Exercises and Recommendations - Dias, Gonçalo Nuno Figueiredo; Couceiro, Micael Santos (Springer International Publishing : Imprint: Springer, 2017)
This book presents an analysis of active ageing and physical activity from a multidisciplinary perspective. With descriptions of exercises, adequately illustrated with pictures, this book shows that regular physical activity reduces the prevalence of chronic diseases associated with ageing, as well as the risk of morbidity and mortality of the elderly. It confirms that exercise programs minimize the psychomotor decline, prevent the loss of functionality, inability and dementia, and foster significant gains in health and well-being, leading to increased quality of life of the elderly.
Keywords: Social sciences.; Medical research.; Occupational therapy.; Aging.; Quality of life.; elektronické knihy; electronic books